Quality index of dimension stones for application in building industry using technological characterization lab tests (Research, Society and Development, 2022)
Dimension stones have been used in many different environments, like airports, shopping malls, commercial buildings and houses, due to their beauty and quality. However, the choice of the ideal material for application in a given environment is a challenging decision. Esthetic patterns determine the choice in most of the cases, instead of the physical and mechanical properties, which can cause damages and even accidents. Thus, this research aims to propose a quality index using technological characterization lab tests established by international and national regulations. This index can be used to help practitioners in the choice of the proper dimension stone for a given environment, minimizing pathologies. An extensive database encompassing many lab tests for technological characterization of dimension stones was used in this research.